ANALISA PERBANDINGAN KINERJA PERBANKAN SYARIAH DAN KONVENSIONAL PRA DAN PASCA COVID-19 - Nasution, Muhammad Syafril; Husni Kamal (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2021)
The Purpose of this study is to compare the differences between the development of Islamic banking performance and conventional banking performance in the previous few months before and after the covid-19 pandemic. this analysis contrasts the finding of previpus studies with the two formas of banking that were not related to the covid pandemic in the preceding year. Multiple financial ratios were used in previous studies to determine the financial efficiency of banks. Based on previous research, there are several ratios used to see the performance of both Islamic banking and conventional banking, including liquitdy ratios, profitability ratios, solvency ratios, and efficiency ratios.